Instructional case: Worldwide Shipping Corporation Ltd: Early or late adoption of a new international accounting Ssandard? - TAN, Pearl (Institutional Knowledge at Singapore Management University, 1999)
The management of Worldwide Shipping Corp. Ltd. is confronted with a dilemma when a new international accounting standard on leases is introduced which contains a transitional provision allowing firms to defer implementation for a period of 4 years. Students are required to put themselves in the position of managers who have to weigh the adverse impact of early adoption of the new accounting standard against a responsibility for fair financial reporting. The case aims to provide students with a better understanding of the impact of off-balance sheet transactions on a firm's financial statements. The case requires students to examine implications of accounting choice on management compensation and debt-contracting costs, as well as the perplexing problem of recognition in financial statements versus footnote disclosures. The case provides students with a useful exercise in the mechanics of effecting a change in accounting method using the retroactive method.